The characterization of complete mitochondrial genome and phylogenetic relationship within Rattus genus (Rodentia: Muridae). (April 2017) - Wei, Haixue; Li, Fengjun; Wang, Xuming; Wang, Qiong; Chen, Guiying; Zong, Hao; Chen, Shunde
Abstract: The genus Rattus is one of the main pest genus of rodent. Most species of the genus carry all kinds of pathogenic bacteria to human being. They are traditionally considered to be a least understood group. The complete mitochondrial genome of the White-Footed Indochinese Rat, Rattus nitidus was determined in this study. The characterization of mitochondrial genomes of Rattus genus was also analyzed based on comprehensive comparison. The result of evolutionary patterns of protein-coding genes (PCGs) suggested purifying selection was the predominant evolutionary forces in the mitochondrial genomes of Rattus genus. The NADH dehydrogenase 4 gene (ND4) showed a highly elevated Ka/Ks ratio compared to the other protein-coding genes, which indicated ND4 was most likely under relaxed selection pressure. Phylogenetic analysis provided a well-supported outline of Rattus genus, and revealed two groups in the genus. R. nitidus had a sister relationship with R. norvegicus . Highlights: The complete mitochondrial genome of Ratta nitidus is sequenced. The characterization of mitochondrial genomes of the Rattus genus is analyzed. Purifying selection is the predominant evolutionary forces in Rattus genus. Rattus genus is divided into two groups.